Analysis of Market Value and Profitability to Return Shares in Manufacturing Companies Listed on BEI - Dahlia Pinem (Budapest International Research and Critics University, 2022)
The capital market acts as a source of financing for businesses and investment for investors. Therefore, it is necessary to assess the performance of the company that will be used as a place of investment by analyzing the company's financial statements. This study aims to analyze the Market Value and Profitability of Stock Returns on the Indonesia Stock Exchange. Market Value is proxied by Earning per Share, Price Book Value, and Price Earning Ratio, and Profitability is proxied by Return on Assets and Return on Equity. The population of this study are companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period. The sampling technique in this study used a purposive sampling technique. Analysis using Microsoft Excel 2013 using the E-Views 11 program to test the hypothesis with Panel Data Regression Analysis, and the confidence level used is 5%. The results of the t test show that only the ROA, ROE, and PBV variables have a significant effect on stock returns, while the EPS and PER variables have no significant effect on stock returns. Likewise, the results of the F test show that roa, roe, PBV, EPS, and PER simultaneously all affect stock returns.